Destructive effect of train load on rust-cracked sleepers at mesoscopic scale - Zhihong Wang; Hao Jin; Donghao Yin (Case Studies in Construction Materials, 2023)
Under the coupling effect of environment and stray current, concrete railway sleepers will have rust and cracks. The dynamic load of trains exacerbates the crack propagation in the sleepers, thereby reducing their service life. To address this problem, this paper employed the Mesoscale Concrete Model with Real Aggregate Geometry to construct a three-dimensional micro-model of the concrete sleeper, examined the distribution of corrosion current density within the sleepers under various corrosion durations, and investigated the effect of rust accumulation on the steel surface on the sleeper cracking. Moreover, the damage evolution of corroded sleepers under train load was studied. The research results revealed that: (1) The corrosion current density increased rapidly in the early stage of corrosion. After 30 years of corrosion, 10 % of the steel reinforcement protective layer cracked, while after 50 years of corrosion, the cracked area reached 40 %. (2) The maximum thickness of rust accumulation in the middle of the sleeper rebar was 0.4 mm after 30 years of corrosion, and 0.6 mm after 50 years of corrosion. (3) Under the train load, the maximum instantaneous damage increase of the sleepers was 0.314 %, and the maximum damage increase within the 30-year corroded sleepers was 0.05 %.